Further delineation of EBF3-related syndromic neurodevelopmental disorder in twelve Chinese patients - Zhu, Jitao; Li, Wenhui; Yu, Sha; Lu, Wei; Xu, Qiong; Wang, Sujuan; Qian, Yanyan; Guo, Qiufang; Xu, Suzhen; Wang, Yao; Zhang, Ping; Zhao, Xuemei; et al. (Frontiers in Pediatrics, 2023)
Neurodevelopmental disorders (NDDs) have heterogeneity in both clinical characteristics and genetic factors. EBF3 is a recently discovered gene associated with a syndromic form of NDDs characterized by hypotonia, ataxia and facial features. In this study, we report twelve unrelated individuals with EBF3 variants using next-generation sequencing. Five missense variants (four novel variants and one known variants) and seven copy number variations (CNVs) of EBF3 gene were identified. All of these patients exhibited developmental delay/intellectual delay. Ataxia was observed in 33% (6/9) of the patients, and abnormal muscle tone was observed in 55% (6/11) of the patients. Aberrant MRI reports were noted in 64% (7/11) of the patients. Four novel missense variants were all located in the DNA-binding domain. The pathogenicity of these variants was validated by in vitro experiments. We found that the subcellular protein localization of the R152C and F211L mutants was changed, and the distribution pattern of the R163G mutant was changed from even to granular. Luciferase assay results showed that the four EBF3 mutants' transcriptional activities were all significantly decreased (p<0.01). Our study further expanded the gene mutation spectrum of EBF3-related NDD.